Conversational Implicature in Political Discourse: A Pragmatic Analysis of YouTube Podcast How America Lost Faith - Jesika Wati Patrisia Purba; Afriana (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study examines how conversational implicature operates within the YouTube podcast How America Lost Faith in Everything, exploring how implied meanings reflect political distrust and shape audience interpretation. Drawing on Grice’s Cooperative Principle and Levinson’s pragmatic framework, this research analyses selected segments from the podcast to identify implicatures used to express criticism toward institutional authority. Using a qualitative descriptive method, the researcher transcribed episodes and conducted thematic coding to uncover implicit messages embedded in the discourse. The findings reveal that implicature serves as a subtle rhetorical tool for shaping socio-political narratives expressing scepticism, irony, and ideological stance without direct confrontation. This study contributes to understanding how digital political communication constructs meaning through indirectness and how YouTube discourse influences public perception of trust in institutions.